Pengaruh Beban Kerja Dan Kompetensi Kerja Terhadap Produktivitas Kerja Pegawai - Dona Mailoa, Mary; Sunu Kanto, Dwi (GEMA EKONOMI, 2023)
This study aims to determine the effect of workload and work competence on work productivity for all the employees in General Bureau of the Ministry of Manpower which is mediated by work motivation. The approach used in this research is a quantitative approach. The population used in this study as many as 212 employees, and the number of sample in this study are 140 samples and this study using SmartPLS as an analysis method. The technique used in data collection uses a questionnaire by distributing list of questions to respondents. The results showed that workload has a negative and significant effect on work productivity. Work motivation has a positive and significant effect on work productivity and mediates fully workload on work productivity. Work competence has a positive and significant effect on work productivity. Work motivation mediates partially work competence on work productivity